2021
DOI: 10.1016/j.amjmed.2021.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends and Patient Characteristics Associated with 30-Day Hospital Readmission Rates after a First Acute Myocardial Infarction

Abstract: BACKGROUND: Limited data exist about relatively recent trends in the magnitude and characteristics of patients who are re-hospitalized after hospital admission for an acute myocardial infarction. This study examined trends in the frequency and sociodemographic and clinical characteristics of patients readmitted to the hospital within 30 days after an initial acute myocardial infarction. METHODS: We reviewed the medical records of 3116 individuals who were hospitalized for a validated first acute myocardial inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…[23][24][25] In 9406 STEMI patients between 2002 and 2008, Kaul et al found that 13.6% of the cohort developed AHF during the index hospitalization and a cumulative rate of 23.4% was noted at 1 year. 25 Other contemporary registries have shown similar AHF incidence after STEMI (9.9%-14.6%), [22][23][24] consistent with the incidence of this event in our cohort (10.4%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[23][24][25] In 9406 STEMI patients between 2002 and 2008, Kaul et al found that 13.6% of the cohort developed AHF during the index hospitalization and a cumulative rate of 23.4% was noted at 1 year. 25 Other contemporary registries have shown similar AHF incidence after STEMI (9.9%-14.6%), [22][23][24] consistent with the incidence of this event in our cohort (10.4%).…”
Section: Discussionmentioning
confidence: 99%
“…22 In more contemporary registries, however, AHF occurrence has decreased, probably due to the adoption of urgent reperfusion strategies which can decrease the amount of irreversible myocardial damage. [23][24][25] In 9406 STEMI patients between 2002 and 2008, Kaul et al found that 13.6% of the cohort developed AHF during the index hospitalization and a cumulative rate of 23.4% was noted at 1 year. 25 Other contemporary registries have shown similar AHF incidence after STEMI (9.9%-14.6%), [22][23][24] consistent with the incidence of this event in our cohort (10.4%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the past few years, acute myocardial infarction (AMI) has deprived millions of people of their health. , When patients suffer AMI, the symptoms are breathing difficulty, nausea, faintness, breaking out in a cold sweat, and tiredness. If AMI cannot be recognized in time, heart failure, arrhythmias, cardiogenic shock, and cardiac arrest can occur in patients. In time, the detection of AMI biomarkers should be given much more attention, mainly focusing on designing a fast, simple, and convenient detection method. Although aspirin is an effective curing drug for AMI, overuse of aspirin can cause profound side effects.…”
Section: Introductionmentioning
confidence: 99%